Transforming education through values: a teacher capability framework - Ročāne, Maija; Jurs, Pāvels; Bethere, Dina; Usča, Svetlana; Konovalenko, Tetiana (Society Register, 2026)
In the context of rapid societal and educational transformation, this study explores the influence of educational values on teachers’ personal, professional, organizational capabilities, and their capability for change. Educational values reveal the goals of education in both individual and collective terms. The individual responsibility of the teacher for affirming and implementing value learning becomes relevant, as well as the awareness of values, since a person can act in accordance with their own values without even being aware of them. The aim of this study is to characterize theoretical perspectives on the processes of value acceptance, affirmation, and implementation within contemporary educational contexts, and to empirically investigate the extent to which educational values influence teachers’ personal, professional, and organizational capabilities, including their capability for change. The study employs a quantitative approach with a survey of 169 Latvian teachers assessing the perceived impact of education on self-awareness, creativity, well-being, and societal development. Results indicate that while teachers recognize the value of education in enhancing personal growth and societal contribution, challenges remain in fostering creativity, openness to change, and public support for the profession. The findings underscore the importance of aligning educational values with policy, cultural awareness, and lifelong learning to strengthen teachers’ capability frameworks. The study concludes that values are central to educational transformation, influencing not only teaching practices but also the broader mission of education in shaping resilient, inclusive, and forward-looking societies. The data analysis highlights that cultural awareness and the creation of a knowledge society become important values for achieving the goals of education, justifying their importance not only to students and teachers, but also to society as a whole.